Pengembangan Strategi Bisnis Toko A. Fauzi: Pendekatan Analisis Swot Dan Value Proposition Canvas - Clara, Nandita Julia; Abdilla, Mohammad (LPPM Universitas Dharma Andalas, 2025)
This study analyzes the business strategy of Toko A. Fauzi using the SWOT and Value Proposition Canvas (VPC) approaches to evaluate the store's position in market competition and formulate a development strategy. The SWOT analysis reveals the store's key strengths such as competitive pricing, friendly customer service, a wide product variety, and partnerships with reliable suppliers. However, the store faces weaknesses such as stock limitations, long queues at the cashier, lack of promotion, and an underdeveloped online shopping system. Opportunities for expansion include collaboration with new suppliers, utilizing social media for promotion, and developing delivery services. However, there are external threats such as a shift in shopping behavior towards digital platforms, supply chain issues, and competition from stores offering more attractive loyalty programs. The VPC analysis indicates that the products and services offered by Toko A. Fauzi align with customer needs, which desire affordable prices, stable stock, and a convenient shopping experience. Based on the SWOT analysis, Toko A. Fauzi is in a progressive strategic position, with an IFE score of 3.31 and an EFE score of 3.71, indicating dominant internal strengths and the ability to capitalize on opportunities and address threats. For development, it is recommended to improve stock management, enhance payment and delivery systems, and expand digital marketing strategies and the online shopping platform. By implementing strategies based on SWOT and VPC, Toko A. Fauzi is expected to strengthen its competitiveness and achieve sustainable business growth.